The Role of Translation in the Hungarian as a Foreign Language Class: A Case Study of Hungarian Language Classes of Stipendium Hungaricum Scholarship Holders from the Perspective of the Students and the Language Teachers - Zsolnai, Márton (Technical Languages and Translation, 2023)
The purpose of the research is to map the place and role of the Grammar-Translation method in Hungarian language classes. This is a method with a long history, but it is considered outdated among the modern trends of language pedagogy. In my research, I used a questionnaire survey to examine the attitudes and impressions of the Stipendium Hungaricum scholarship holders (95 participants) who take beginner Hungarian language classes at the Hungarian University of Agriculture and Life Sciences and those of the language teachers who teach Hungarian as a foreign language (5 participants) on five campuses of our university. Results show that the language teachers at the institution know the principles of modern language pedagogy well, but in order to support the learning process more, they may use the positive elements of the grammar-translation method as well. In the Hungarian classes for beginners, although it is more professional to teach without an intermediary language, planned translation and grammatical analysis for specific learning goals can also be useful in certain cases. The beliefs of the students and the teachers regarding grammatical elements and the practical implementation of translation in the language classes in most of the cases show a similar pattern. However, the comparative analysis also revealed some important differences between the viewpoints of the two examined groups.